Association of atopy with disease severity in children with Mycoplasma pneumoniae pneumonia - Bian, ChenRong; Li, SongTao; Huo, ShaoHu; Yang, BeiBei; Wang, PingPing; Li, WenHong; Ding, ShengGang (Frontiers in Pediatrics, 2023)
Background: Mycoplasma pneumoniae pneumonia (MPP) is common among children, but the impact of atopy on MPP severity in children is unknown. This study investigated whether atopic vs. nonatopic children had greater MPP severity.: Retrospective analysis was conducted on 539 (ages 3-14 years) patients who were hospitalized in the First Affiliated Hospital of Anhui Medical University for MPP between January 2018 and December 2021, 195 were atopic and 344 were nonatopic. Of them, 204 had refractory MPP, and 335 had general MPP. And of atopic children, 94 had refractory MPP, and 101 had general MPP. Data on demographic and clinical characteristics, laboratory findings, clinical treatments were analyzed.Results: Significantly more boys with MPP were atopic than nonatopic (P<0.05).More atopic (than nonatopic) children presented with prolonged fever and hospitalization, severe extra-pulmonary complications, asthma attaking, steroid and oxygen treatment, and increased IgE levels (all P<0.05). In atopic (vs. nonatopic) children with MPP, the incidence of sputum plugs under the fiberoptic bronchoscopy and lobar pneumonia was significantly increased and required bronchoscopy-assisted and steroid therapy. Compared with nonatopic children, more atopic children developed refractory MPP (P<0.05). Prolonged fever and hospitalization, severe extra-pulmonary complications, lymphocyte count, procalcitonin and lactate dehydrogenase levels, and percentages of atopy were all significantly higher (P<0.05) among children with refractory MPP vs. general MPP. Moreover, Prolonged fever and hospitalization, lymphocyte count, procalcitonin and lactate dehydrogenase levels, and the treantment of steroid were all significantly higher (P<0.05) among atopic children with refractory MPP vs. general MPP. Spearman correlation analysis showed strong associations between atopy and male sex, length of hospital stay, fever duration, IgE level, wheezing, lobar pneumonia, refractory MPP, and treatment with oxygen, hormones or bronchoscopy (P<0.05).Conclusions: Atopy may be a risk factor for and was positively correlated with the severity of MPP in children.